THE EFFECT OF FOOT EXERCISE ON FOOT SKIN TEMPERATURE AND PERIPHERAL FOOT NEUROPATHY IN DIABETES MELLITUS PATIENTS AT SAWAH LEBAR PUBLIC HEALTH CENTER BENGKULU IN 2023 - Aji Setya Guna Darma Aji; Pauzan Efendi; Efrizon Hariadi; Erni Buston; Noni Buston (Proceeding B-ICON, 2023)
Diabetes Mellitus (DM) is a disease characterized by hyperglycemia and impaired carbohydrate, fat, and protein metabolism associated with an absolute or relative deficiency of the work ofinsulin secretion. The most common complication of DM is peripheral neuropathy characterized by decreased sensitivity and changes in foot temperature. The recommended activity to increase sensitivity and normalize foot temperature is diabetic foot gymnastics. The purpose of this study was to determine whether there was an effect of foot gymnastics on foot skin temperature and peripheral foot neuropathy of DM sufferers at the Sawah Lebar Health Center in Bengkulu City. This type of research is a quasi experiment. With a total sample of 32 people divided into two groups, namely the intervention group of 16 people and the control group of 16 people. The sampling technique in this study was taken using concecutive sampling. The instruments used are Thermomether Gun Infrared and monofilament test. Statistical tests using mann-whitney showed a p value of peripheral foot neuropathy of 0.05 (p value ? 0.05) and p value foot skin temperature 0.001 (p value ? 0.05) so that it can be interpreted that there is adifference in the average of peripheral foot neuropathy and foot skin temperature before and after treatment in the intervention group and control group. So it can be concluded that there is an influence of foot gymnastics on foot skin temperature and peripheral foot neuropathy in patients with DM.